Analysis of the Influence of Mobile Marketing and Social Media Marketing on Purchase Intention with Customer Engagement as an Intervening Variable in the Property Industry - Maula Matin; Patria Laksamana (Journal of Social Research, 2023)
This study is entitled "Analysis of the Effect of Mobile Marketing and Social Media Marketing on Purchase Intention with Customer Engagement as an intervening variable in the Property Industry". The two variables that will be studied in this study Mobile Marketing and Social Media Marketing are used as independent variables. The Purchase Intention variable as the dependent variable and the Customer Engagement variable as the intervening variable. The purpose of this study is to obtain an overview of Mobile Marketing and Social Media Marketing and analyze the relationship of these two variables to Purchase Intention. The empirical study was conducted on internet users in the Jabodetabek area with internet use focused on finding information related to property. The research methods used are survey methods and data collection methods through questionnaires. This study used a sample of 100 respondents. The data analysis method uses SEM (Structural Equation Model) from AMOS 22.0 statistical software. The results of this study show that mobile marketing and social media marketing have a positive impact on customer engagement. From this study it was also found that mobile marketing and social media marketing have no effect on purchase intention. The final conclusion of the study, mobile marketing and social media marketing have a positive impact on the property industry. The presence of both is able to reach a wider market so it needs to be maximized in use.